Analisis Perbandingan Orientasi Agregat DanDistribusi Void Menggunakan Agregat Baru DanRap Yang Dipadatkan Dengan Alat PemadatRoller Slab - Kristianto, Erwin; , Ir. Sri Sunarjono, M.T, Ph.D; , Senja Rum Hernaeni, S.T, M.T (2017)
The extensive damage to roads in Indonesia is the biggest problem facing the field of land transport, it can happen as a result of excessive vehicle loads or unfavorable drainage system, to deal with this problem the need for improvements to enhance the strength and density of road construction. Results of asphalt scratching can still be recycled as asphalt pavement or generally called as RAP. Material is quite good if the spread of the aggregate and void distribution is well distributed. This research aims to determine the comparison of orientation aggregate and void distribution RAP and new aggregate mixtures. This study used methods and the compactor used Slab Roller. The materials used RAP and new aggregate gradations have been likened. On the orientation aggregate test, the specimen is cut horizontally into three sections and vertically into two parts with a marker stone aquarium and glass coordinates to facilitate the reading of the stone displacement after compacted, whereas the void distribution test using the test object whole and cut into 3 layers. Based on the result analysis of orientation aggregate test obtained the orientation of new aggregate and RAP, the stone which moves farthest e was on the top layer, this happens because the upper layer move during the compaction process. Stone movement in the new aggregate look no farther than the aggregate movement of RAP, it can be concluded that the new aggregate mixture more freely move. While RAP material cut into 3 parts VIM values obtained on 45 passing top layer 11.28%, middle of 12.45%, bottom 13.42%, the result of full specimen test 12.58%. In the new aggregate mixture top layer 11.45%, middle 11.85%, bottom 12.61% the result of full specimen test 10.66%. In the void distribution test can be concluded that the new aggregate the void distribution is well distributes and VIM value smaller than RAP aggregate.